The Behavioral attributesAbout Nuptialsin Islam (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
Allah has indeed created man and woman to be the natural counterparts of the other, they are natural companions so He has destined that they will find comfort and repose with one another. The foundation of a Muslim marriage is that the physical, emotional and mental bonding and companionship must be firmly based upon love and compassion, only then can husband and wife truly find comfort in one another. For this purpose Islamic guidelines also lead and viewed the marriage relationship as private part in life and a source of human reproduction. It is clear concept the husband and wife must seek to sexually satisfaction through lawful way only. Sex is a human desire that should be fulfilled in any way and Islam does not take the negligence about this vital need so he gave his decent consideration about sex experience. The marriage concept in Islam does not mean the sexual satisfaction only but the both of should be receptive to another needs, and the husband should remember Allah to purify his mind before intercourse and they are commanded not to treat their wives harshly for the purpose of getting back anything. The Non-Muslims who have raised some objection about Islamic concept about sex with so many unfair and groundless accusations. We have trying to introduce Islamic ideas about sex in human life. If the Islamic point of view becomes clear in the minds of non-Muslim, so hoped that they would understand the Islam. My first attempts to present the Islamic point of view about sex specific man-woman relationship. And hope that article would offer a general view for those who are interested to know the stand point about this important social issue.